A Role for the Val291 Residue within the Transmembrane Domain 2 in Diltiazem- and TMB-8 [3,4,5-Trimethoxybenzoic Acid 8-(Diethylamino)octyl Ester]-Mediated 5-Hydroxytryptamine Type 3A Receptor Regulations - Lee, Byung-Hwan; Choi, Sun-Hye; Pyo, Mi Kyung; Shin, Tae-Joon; Hwang, Sung-Hee; Kim, Bo-Ra; Lee, Jun-Ho; Rhim, Hyewhon; Kim, Hyoung-Choon; Nah, Seung-Yeol (PHARMACEUTICAL SOC JAPAN, 2009)
Previous reports have shown that diltiazem and TMB, calcium channel antagonists, inhibit 5-hydroxytryptamine type 3A (5-HT3A) receptor-mediated currents (I5-HT)in cell lines and in heterologously expressed Xenopus oocytes. In the present study, we sought to elucidate the molecular mechanisms underlying diltiazem- and TMB-induced 5-HT3A receptor regulations. We used the two-microelectrode voltage clamp technique to investigate the effect of diltiazem and TMB on 5-HT-mediated ion currents in Xenopus oocytes expressing wild-type or 5-HT3A receptors harboring mutations in the gating pore region of transmembrane domain 2 (TM2). In oocytes expressing wild-type 5-HT3A receptors, diltiazem and TMB dose-dependently inhibited I5-HT peak with an IC50 of 71.4 +/- 4.9 and 4.5 +/- 0.3 mu m, respectively. Among various mutants of TM2, mutation V291A greatly attenuated and abolished the TMB- and diltiazem-induced inhibition of peak I5-HT, respectively. Mutation V291A also induced constitutively active ion currents in the absence of 5-HT. Diltiazem and TMB inhibited constitutively active ion currents in a dose-dependent manner. The IC50 values of constitutively active ion currents in V291A receptors were 165.3 +/- 11.1 and 6.6 +/- 0.5 mu M for diltiazem and 3,4,5-trimethoxybenzoic acid 8-(diethylamino)octyl ester (TMB-8), respectively. Results of site-directed mutagenesis experiments suggest that the Val291 residue could be a candidate for common interaction site for diltiazem- and TMB-8-mediated 5-HT3A receptor regulations.
Keywords: NICOTINIC ACETYLCHOLINE-RECEPTOR; 5-HT3 RECEPTOR; ION; CHANNELS; PORE; BLOCKERS; POTENT; SITES; ESTER